Canine hepacivirus and idiopathic hepatitis in dogs from a Dutch cohort. Issue 12 (5th June 2014) - van der Laan, L. J. W.; de Ruiter, P. E.; van Gils, I. M.; Fieten, H.; Spee, B.; Pan, Q.; Rothuizen, J.; Penning, L. C.
Summary Liver diseases are highly prevalent in the general dog population, though the etiology is often unknown. Recently a homolog of human hepatitis C virus was discovered in dogs with respiratory infections. Although this canine hepacivirus (CHV) was detectable in some liver samples, a clear link with liver disease has not been established. A recent study by Bexfield et al. showed that in a large cohort of dogs from the UK with idiopathic hepatitis, no evidence can be found for exposure to, or carrier state of CHV both in liver and in serum. The authors however state that 'the absence of CHV infection on dogs from the UK might not represent the global ecology of the virus'. We investigated CHV‐infection in 267 liver biopsies from 120 dogs idiopathic hepatitis and 135 control animals, in a population from the Netherlands. Using a highly sensitive PCR assay for CHV‐NS3, no CHV was detected in all 267 liver samples. Our data show that the lack of association between canine hepacivirus and chronic liver disease in dogs is not limited to the UK, but is also found in an independent cohort from the European continent.